If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6xy + 3x + -2yx = 0 Reorder the terms: 3x + 6xy + -2xy = 0 Combine like terms: 6xy + -2xy = 4xy 3x + 4xy = 0 Solving 3x + 4xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'x'. x(3 + 4y) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3 + 4y)' equal to zero and attempt to solve: Simplifying 3 + 4y = 0 Solving 3 + 4y = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4y = 0 + -3 4y = 0 + -3 Combine like terms: 0 + -3 = -3 4y = -3 Add '-4y' to each side of the equation. 4y + -4y = -3 + -4y Combine like terms: 4y + -4y = 0 0 = -3 + -4y Simplifying 0 = -3 + -4y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| -2-4y=-10 | | 2x+20=5x-7 | | -5x-9y=-20 | | 3c+10=28 | | y=45xz+100xz+10z | | y=45xz+100+10z | | y=45xz | | 9-3(x+2)= | | 6x-8=16+4x | | -21x^2-33x+18= | | 270+16x=14x | | y+16=12 | | 4w^2-8wx-21x^2= | | 0.5cos(x)+0.08cos(2x-0.1)=0 | | 13x^2-27+28=0 | | 3m+23=8m-2 | | 4(w+1)+w=5(-1)+9 | | (h*f)(1)=4x-1-x+4 | | a^3y+1=0 | | x-2=7x+50 | | 8r+3=5r+12 | | -3(2x+4)=0 | | x=6-0.5y | | 7(11-8)=21 | | 7(p-8)=21 | | -7x=-49+98 | | 2x+2(2)=-10 | | 45+x=602 | | (3r-2s)(3r-2s)= | | 116-w=294 | | -8x-2(-1.5)=-13 | | -8(2)-2y=-13 |